Lamprista gen. nov. of Lecithoceridae (Lepidoptera, Gelechioidea) from New Guinea, with descriptions of two new species - Park, Kyu-Tek; Lee, Sangmi (Zootaxa, 2013)
Lamprista gen. nov., morphologically allied to Crocanthes Meyrick, 1886, is described from New Guinea, based on the type species, L. emmeli sp. nov., and an additional species, L. ortholepida sp. nov., is described. Illustrations of the imagos, male and female genitalia, and wing venation of the new species are given. A new combination from Crocanthes is proposed: Lamprista hemipyra (Meyrick, 1938), comb. nov. A key to the species of Lamprista is given.